Civil Proof through the Judge's Inspection - Nada Mohamed Al-Maazmi, (Journal of Legal Sciences, 2024)
In Federal Decree-Law No. 35 of 2022, the legislator in the United Arab Emirates introduced the Law of Evidence in Civil and Commercial Transactions, which outlines methods and means of evidence, including inspection. This legislation grants the UAE court the authority to issue an inspection order, either on its own initiative or at the request of the parties involved in the case. The court has discretionary power to appoint one of its judges to carry out the inspection or to appoint an expert to do so.The study problem focused on the need for amendments to the articles related to judicial inspection to eliminate ambiguity and avoid misinterpretation, thereby ensuring the legislator’s intent is fulfilled. The study analyzed the subject of civil evidence through judicial inspection using an analytical approach, examining all relevant legal texts and their judicial applications to achieve the study’s goals and resolve its issues.The study was divided into two sections. The first section addressed the scope of evidence by judicial inspection, discussing the court's powers in inspection-based evidence in the first topic and the subject matter of judicial inspection in the second topic. The second section covered the procedures for judicial inspection, with the first topic dealing with subsidiary procedures for judicial inspection, and the second topic discussing primary procedures for inspection. The study concluded with findings, the most important of which was that the court’s authority to appoint a judge or expert for inspection involves different legal rules for each type. The most important recommendations of the study were the need to provide for the inspection of persons, and the need to introduce some amendments to the texts under study to remove the confusion.